A Good Place to Bury Bad News? Hiding the Detail in the Geography on the Labour Party's Website. - Dorling, Danny; Eyre, Heather; Johnston, Ron (Political Quarterly)
The substitution of statistics on a British Labour Party website to place the party in a good light in 2002 is investigated. How such substitution was performed, and the rules of political statistical manipulation, are discussed. It is demonstrated how even figures manipulated to exhibit the work of a political party in a good light can be employed to cast doubts on the party's claimed achievements.